STUDI EPIDEMIOLOGI TENTANG KEAMANAN VAKSIN COVID-19 PADA IBU HAMIL DAN IBU MENYUSUI - Ivan Idul Jana; Salman Salman (Pusat Riset dan Inovasi Nasional, 2023)
COVID-19 disease has spread around the world. Some events progress to acute respiratory distress syndrome or more severe forms of the disease leading to death. Pregnant women with COVID-19 are known to have a high risk of being admitted to the ICU. An increase in premature births is still observed in cases of complications caused by COVID-19. Vaccination is done to stimulate the body to form antibodies specific to the virus. However, the side effects of this vaccination need to be tested, especially its safety for pregnant and lactating women. The purpose of writing this article is to determine the safety of several types of COVID-19 vaccinations for pregnant women and nursing mothers. The method used is a literature study of previous research2. The results of this literature study found that the type of vaccination that is recommended for pregnant and lactating women is Sinovac.